The influence of familial factors on the association between IQ and educational and occupational achievement: A sibling approach. (15th October 2019) - Hegelund, Emilie Rune; Flensborg-Madsen, Trine; Dammeyer, Jesper; Mortensen, Laust Hvas; Mortensen, Erik Lykke
Abstract: The present register-based study investigated the influence of familial factors on the association of IQ with educational and occupational achievement among young men in Denmark. The study population comprised all men with at least one full brother where both the individual and his brothers were born from 1950 and appeared before a draft board in 1968–1984 and 1987–2015 (N = 364, 193 individuals). Intelligence was measured by Børge Priens Prøve at age 18. Educational and occupational achievement were measured by grade point average (GPA) in lower secondary school, time to receiving social benefits at ages 18–30, and gross income at age 30. The statistical analyses comprised two distinct statistical analyses of the investigated associations: A conventional cohort analysis and a within-sibship analysis in which the association under investigation was analysed within siblings while keeping familial factors shared by siblings fixed. The results showed that an appreciable part of the associations of IQ with educational and occupational achievement could be attributed to familial factors shared by siblings. However, only the within sibling association between IQ and GPA in lower secondary school clearly differed from the association observed in the cohort analysis after covariates had been taken into account. Highlights: Family factors explain part of the association of IQ with educational achievement. Family factors explain part of the association of IQ with occupational achievement. Most of the influence of family factors can be ascribed to 8 measurable covariates. Unmeasured, proximal family factors seem to mainly operate during upbringing.